Stable isotopes (δ18O and δ13C), trace and minor element compositions of Recent scleractinians and Last Glacial bivalves at the Santa Maria di Leuca deep-water coral province, Ionian Sea - López Correa, Matthias; Montagna, Paolo; Vendrell Simón, Begoña; McCulloch, Malcom; Taviani, Marco (Deep Sea Research Part II: Topical Studies in Oceanography, 2010)
Special issue The APLABES Programme: Physical, Chemical and Biological Characterization of Deep-Water Coral Ecosystems from the Ionian Sea (Mediterranean).-- 16 pages, 13 figures, 3 tables, 2 appendix The aragonitic skeletons of bathyal cold-water corals have a high potential as geochemical in situ archives for paleoceanography. Oxygen isotopes and stable carbon isotopes (δ18O and δ13C) have been analyzed, as well as trace and minor element compositions (e.g. Mg/Ca, Sr/Ca, U/Ca, B/Ca and P/Ca) in Lophelia pertusa, one of the most important frame-builders at the Santa Maria di Leuca (SML) deep-water coral hotspot in the Central Mediterranean. The Apulian Bank is swept by strong currents of the Adriatic Deep Water Outflow. The temperature of 13.9 °C is the highest temperature recorded for L. pertusa and provides an important end-member of environmental conditions for geochemical analyses on living Atlantic and Mediterranean cold-water corals. Temperature and salinity (38.77 PSU) are stable throughout the year, and thus virtually no changes should be observed in the stable oxygen isotope signal-if the coral precipitates its skeleton in equilibrium with seawater. We measured various marine properties, such as the seawater oxygen isotope composition (δ18Osw), stable carbon isotope composition (δ13CDIC) of dissolved inorganic carbon (DIC), and dissolved inorganic nutrient concentrations (PO4, NO3, NO2, NH3 and SiO2). Bottom water at the coral sites shows a mean oxygen isotope composition of 1.47‰ δ18Osw-VSMOW, and δ13CDIC showed a mean of 1.1‰ VPDB. A section of a living L. pertusa with a thick theca calcification was probed with a Merchantek MicroMill at a high spatial sampling resolution with 10 samples per 1 mm. This reduced the signal-smoothing inherent to conventional sampling. The δ18Oag of coral aragonite ranges between -2.0‰ and +2.8‰ VPDB and the δ13Cag ranges between -7.77‰ and +1.47‰ VPDB. The Gaussian data distribution for both parameters, including heavy equilibrium values, suggests the completeness of ...